Pengaruh Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Yang Termasuk Dalam Jakarta Islamic Index - Endang Mahpudin (Accounthink, 2017)
Taxes have a direct impact on reduction of a company's profits. Tax levy which the government should do without harming the public. Given the management's desire to press and make the tax burden as small as possible, so the management tends to minimize tax payments.Earnings management is an effort made by the management to intervene in the preparation of financial statements in order to benefit himself, namely the related companies.This study aims toexamine and obtain empirical evidence on the influence of tax planning on corporate earnings management practices included in the Jakarta Islamic Index.Population research was all the companies joined in the Jakarta Islamic Index. Sampling technique using purposive sampling, the sample with criteria of company that have audited financial statements and ended on December 31 and published in full from 2012-2016. Selection of selected samples of 28 companies. Data analysis using linear regression analysis. The results showed thattax planning had a significant positive effect onearnings management practices of companies included in the Jakarta Islamic Indexwith a magnitude of influence of only 8.9%. Hypothesis testing states theeffect of tax planning on profit management practices. The value of the regression coefficient is positive which indicates that the higher from tax planning, will improve thepractice of earnings managementsignificantly. The influence of tax planning on earnings management practice is 8.9%. The implication of this research such as the management press and make the tax burden as small as possible, so the management tends to minimize the tax payment with various efforts, as long as the activity is still in the applicable taxation regulation.